2007
DOI: 10.1257/jep.21.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Reforms in Continental Europe

Abstract: The fundamental problem of corporate governance in the United States is to alleviate the conflict of interest between dispersed small shareowners and powerful controlling managers. The fundamental corporate governance in continental Europe and in most of the rest of the world is different. There, few listed companies are widely held. Instead, the typical firm in stock exchanges around the world has a dominant shareholder, usually an individual or a family, who controls the majority of the votes. In this essay,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
173
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(184 citation statements)
references
References 28 publications
4
173
0
7
Order By: Relevance
“…See Seligman (2003) for a history of US securities laws and Zitzewitz (forthcoming) for a survey of economic analyses of these laws. Enriques and Volpin (2007) survey corporate governance reforms in Europe.…”
Section: Sarbanes-oxley Act and Other Securities Lawsmentioning
confidence: 99%
“…See Seligman (2003) for a history of US securities laws and Zitzewitz (forthcoming) for a survey of economic analyses of these laws. Enriques and Volpin (2007) survey corporate governance reforms in Europe.…”
Section: Sarbanes-oxley Act and Other Securities Lawsmentioning
confidence: 99%
“…In line with these conclusions, the research explains the strong presence of these devices in continental Europe and East Asia by looking at the limited investor protection of the national regulations in force, and interprets their improvements as able to hamper the employment of disproportional ownership devices (Almeida & Wolfenzon, 2006a;Zattoni & Cuomo, 2010;Faccio, Lang, & Young, 2010;Cuomo et al, 2012). Indeed, in some settings, the law reforms aiming at increasing the investor protection have reflected in a lower use of DOMs (Enriques & Volpin, 2007) because they have limited the incentives to adopt ownership structures separating voting and cash-flow rights, even when the resources available through company performance were large (Saggese, 2013). Thereby, it remains an empirical issue whether past firm outcomes positively or negatively affect the use of disproportional ownership devices.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…streams of literature have emerged. Some studies have emphasized that controlling owners limit the classic agency risk and the managerial opportunism (Roe, 1994) but foster the expropriation of company wealth at the expenses of minority investors (Bigelli & Megoli, 2004;Enriques & Volpin, 2007). Indeed, literature in this strand has suggested that controlling shareholders raise a principal-principal agency problem and can easily extract private benefits of control as the separation between cash-flow rights and voting rights through disproportional ownership mechanisms is wider (Hu & Kumar, 2002;Kang, Kumar, & Lee, 2006;Kumar & Rabinovitch, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no such thing as a universal ideal governance structure, because such structures are constrained by various issues including company laws and codes of conduct (Enriques & Volpin, 2007). A particular CG structure that meets the needs of one company's CSR practices might be inappropriate for others.…”
Section: Csr Governance Structurementioning
confidence: 99%